Efektivitas Kinerja Kepemimpinan Pendidikan dalam Organisasi: Analisis Hakikat Kepemimpinan dan Otoritas Menurut Max Weber - Alifia Annora Qotrun Nada; Rika Dwi Novitasari; Erni Najihah; Shofi Auliyah; Mardiyah Mardiyah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to examine the concept of leadership in educational organizations, analyze the types of authority according to Max Weber, and explain their influence on the effectiveness of educational leadership performance. The study employs a qualitative approach using library research methods through the review of various relevant scholarly sources, including Max Weber’s original works as well as journal articles and other academic books. Data analysis was conducted using content analysis techniques, involving the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that educational leadership is a process of directing, influencing, and managing organizational resources to achieve educational goals effectively. In Weber’s theory, there are three forms of authority: traditional, charismatic, and rational-legal, each possessing distinct characteristics in leadership practice. Traditional authority serves to maintain organizational stability but tends to limit renewal and innovation. Charismatic authority can boost the motivation and work ethic of organizational members, yet it is highly dependent on the leader’s persona. Meanwhile, rational-legal authority fosters professionalism and work efficiency, though it may potentially diminish interpersonal relationships within the organization. The novelty of this study lies in the development of a model integrating Weberian authority that combines all three forms of authority within the context of educational leadership.Keyword: Educational Leadership, Max Weber’s Concept Of Authority, Effectiveness, Educational Organizations